PRAKTIK INSTRUCTIONAL LEADERSHIP KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA PEMBELAJARAN KOLABORATIF DI SEKOLAH DASAR - Fatimah, Iim; Indah Susi Irianti; Wahyu Haspri Nur Taryanti; Darsinah, Darsinah; Wafrotur Rohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to provide an in-depth description of the principal’s instructional leadership practices in fostering a collaborative learning culture at SD Muhammadiyah Plus Semarang. The study is motivated by the importance of instructional leadership in supporting teachers’ professional development, enhancing the quality of teaching and learning processes, and strengthening a collaborative learning culture within the implementation of the Merdeka Curriculum in elementary schools. Instructional leadership is considered a strategic factor in creating a school environment that promotes reflection, collaboration, and continuous improvement in teaching and learning.This research employed a qualitative approach with a case study design to gain a comprehensive understanding of instructional leadership practices within the school’s social, cultural, and organizational context. The participants consisted of the principal, curriculum coordinator, and classroom teachers who were selected through purposive sampling based on their involvement in the school’s instructional programs. Data were collected through semi-structured interviews, participant observation, and document analysis. Data trustworthiness was established through source triangulation, method triangulation, member checking, and an audit trail. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing.The findings reveal that the principal’s instructional leadership was manifested through reflective pedagogical communication, the establishment of teacher learning communities, dialogic academic supervision, and the reinforcement of a collaborative work culture grounded in interpersonal relationships. The study also found that a collaborative learning culture developed through trust, open communication, the sharing of best practices, and teachers’ active engagement in collective reflection. This study contributes to strengthening the concept of relationship-based instructional leadership within the context of Indonesian elementary education. Practically, the findings offer important implications for developing more reflective, humanistic, adaptive, and collaborative school leadership models to enhance learning quality and support sustainable teacher professional development.